Analysis of School Policy Effectiveness in Anticipating Students’ Use of The Internet and Digitalization in Learning Process - Mohzana; Desty Endrawati Subroto; DM Ratna Tungga Dewa; Rinovian; Hadi Prayitno (Jurnal Sistim Informasi dan Teknologi, 2024)
This research aims to understand the points of agreement, tensions, and disputes between students, teachers and schools regarding the use of the Internet by teenagers for educational purposes. This study employs an empirical approach by utilizing survey methods and semi-structured interviews. We obtained data for this research from 100 respondents. According to the analysis’s findings, technology integration in education necessitates adequate training for teachers to be able to integrate technology effectively. Teachers need to not only master technical skills but also understand how to use technology to stimulate students’ critical and collaborative thinking. Holistic digital literacy is the key to preparing students to face the complexity of today’s digital information. Teachers’ role as facilitators is also changing, with technology allowing them to support students in actively engaging in learning and knowledge creation. The importance of diversifying learning sources, including the internet and traditional sources, enriches students’ learning and ensures they are skilled in using a variety of information sources. While there are challenges in adopting technology, proper integration can improve the relevance and quality of learning, preparing young people to face the future more effectively.